Seco-Polycyclic polyprenylated acylphloroglucinols with unusual carbon skeletons from Hypericum ascyron. Issue 22 (31st May 2017) - Kong, Ling-Mei; Long, Xian-Wen; Yang, Xing-Wei; Xia, Fan; Khan, Afsar; Yan, Hui; Deng, Jun; Li, Xian; Xu, Gang
Graphical abstract: Highlights: Polyprenylated acylphloroglucinols, ascyronones A–D, were isolated from Hypericum ascyron . Compounds1 and2 shared an unusual seven-membered carbon core fused with a γ -lactone ring. A biomimetic transformation from hyperibone J (5 ) to ascyronone A (1 ) was performed. All the isolates were decorated with a methyl group at C-5 instead of a prenyl or geranyl group. Abstract: Three new seco -polycyclic polyprenylated acylphloroglucinols (PPAPs), ascyronones A–C (1 –3 ), and a new biosynthetic precursor, ascyronone D (4 ), were isolated from Hypericum ascyron together with three known analogues (5 –7 ). Compounds1 and2, sharing an unusual seven-membered carbon core fused with a γ -lactone ring, could be derived from 1, 9- seco -PPAPs via further rearrangement. A biomimetic transformation from5 to1 was performed by using base-driven retro -Claisen and rearrangement cascade reaction, which further confirmed the structure of1 and shed light to its possible biosynthetic pathway. Interestingly, all these compounds are decorated with a methyl group at C-5 instead of a prenyl or geranyl group in many other PPAPs. The isolates were evaluated for their inhibitory activities against five human tumor cell lines.